On the availability of generic concepts in the context of their non-available naming units (in terms of the Pirahã language) - Попов, Сергій Леонідович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
Certain linguists believe that speakers of the mother-tongues which are considered to be primitive without any nomination of generic concept  have such concepts. The paper is aimed at testing the theoretical substantiation of the statement concerning the available generic concepts in the consciousness in terms of the non-availability of their nomination in the language and specifying the reason of such a statement. A hypothesis is made on the fact that the acceptance of the availability of generic concepts in the consciousness in terms of their non-available nominations in the language is such a wide logical error as substitution of notions meaning the transference of the modern mentality onto the mentality of a primitive man.Analyzing the material of active-structure languages which have only one generalized “living – nonliving” opposition (which includes the Pirahã  language considered in the paper) and which are impossible to generalize in terms of more specific features than living and nonliving signs (due to the prevailing syncretism), in terms of the correlations of structural characteristics of the Pirahã  language with the peculiar non-availability of adjectives and generalized nouns in the language of half-year-old (but not two-year-old) children, in terms of the generalization/non-generalization of colour nomination in the civilized and primitive (including Pirahã) languages, applying the notion of memory, degrees of perception, logics as thinking structure, and abstract nature of thinking (closely connected with the generalization), it is proved that the availability of generic concepts in terms of the non-availability of their definitions (postulated only for the primitive languages) is impossible; and confirmation of that availability is such a substitution of notions today as the transference of the modern civilized mentality onto the primitive mentality.